PENGARUH PENERAPAN STRATEGI QUANTUM TEACHING DAN QUANTUM QUOTIENT TERHADAP HASIL BELAJAR PAI SISWA KELAS VI SD NEGERI 027950 BINJAI - Badriah Badriah (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aims to determine the influence of learning strategy Quantum Teaching on learning outcomes in the field of Islamic Religious Education, the influence of Quantum Quotient learning strategy on learning outcomes of Islamic Religious Education, and differences in learning outcomes in the field of Islamic Religious Education students are taught using Quantum Teaching with Quantum Quotient in Grade VI SD Negeri 027950 Binjai. The research method used quasi-experimental method is a research used to find the effect of certain treatment against others in a controlled condition. In this study also involves two sample groups of each learning Quantum Teaching and Quantum Quotient learning. The population of this research is the students of class VI SD Negeri 027950 Binjai Lesson Year 2016 / 2017.Teknik analysis used in this study is a technique determining the comparison of the acquisition value or average score in each experimental group. The results of this study indicate that: First, Quantum Teaching learning strategy influences on learning outcomes in the field of Islamic Religious Education students grade 6 Elementary School 027950 Binjai. This can be proved by an increase in the average value of pretest results of 34.75 to 62.75 based on postes results. Secondly, Quantum Quotient's learning strategy has an effect on the learning result of Islamic Religion study subject of grade 6 of SD Negeri 027950 Binjai. It can be proved that there is an increase of prestes average value of 33.88 to 72.63 based on postes result. Third, there are differences in student learning outcomes using Quantum Teaching learning strategy with Quantum Quotient. The average value of student learning outcomes using Quantum Teaching learning strategy of 62.75 and using Quantum Quotient learning strategy of 72.63. Thus, the Quntum Quotient learning strategy is better than the Quantum Teaching learning strategy in the field of Islamic Religious Education study in grade 6 students at SD Negeri 027950 Binjai.